Shear Bond Strength of Metal and Ceramic Brackets to Composite Using Single Bond and Universal Adhesive - Pouyanfar, Hoda; Golshah, Amin; Shekarbeigi, Matin (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: This study aimed to assess the shear bond strength (SBS) of metal and ceramic brackets bonded to composite restorations using single bond 5th generation bonding agent and G-Premio Bond universal adhesive. MATERIALS AND METHODS: In this in vitro, experimental study, 60 sound extracted human premolars were veneered with composite and were then randomly divided into four groups (n = 15) of Single Bond + Transbond XT + metal brackets, universal adhesive + Transbond XT+ metal brackets, Single Bond + Transbond XT + ceramic brackets, and universal adhesive + Transbond XT + ceramic brackets. Twenty-four hours after thermocycling, the SBS of brackets was measured using a universal testing machine. The adhesive remnant index (ARI) score was also determined under a stereomicroscope. Two-way ANOVA was used to compare the groups (p <0.05). RESULTS: No significant difference was found in the mean SBS of ceramic and metal brackets or between the two bonding agents (p > 0.05). The interaction effect of type of bracket and type of bonding agent on SBS was not significant (p > 0.05). ARI score I had the highest frequency in Single Bond + Metal bracket group. The highest frequency of ARI score V was noted in the Single Bond + Ceramic bracket group. A comparison of ARI scores of metal bracket groups showed a significant difference between single bond and universal adhesive (p = 0.002). CONCLUSION: Both adhesives can provide adequate SBS for the bonding of metal and ceramic brackets to composite restorations.